2001
DOI: 10.1023/a:1008352123009
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of two-weekly gemcitabine in patients with advanced biliary tract cancer

Abstract: Two-weekly high-dose gemcitabine seems to represent a potentially effective, safe and well-tolerated regimen for the palliative treatment of patients with advanced biliary tract cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
102
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 10 publications
4
102
0
Order By: Relevance
“…Traditionally, 5-fluorouracil-based chemotherapy regimen has been used as an adjuvant therapy for biliary tract malignancies including GB cancer [6,9,20,21]. Recently, gemcitabine-, capecitabine, or S-1-based regimens have been tried, and several studies have demonstrated somewhat promising results from GB cancer [22][23][24][25][26]. However, few comparative analyses of treatments between detailed TNM stages of GB cancer have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, 5-fluorouracil-based chemotherapy regimen has been used as an adjuvant therapy for biliary tract malignancies including GB cancer [6,9,20,21]. Recently, gemcitabine-, capecitabine, or S-1-based regimens have been tried, and several studies have demonstrated somewhat promising results from GB cancer [22][23][24][25][26]. However, few comparative analyses of treatments between detailed TNM stages of GB cancer have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In two phase II trials, both including only small numbers of patients, gemcitabine plus 5-FU/LV and 2 weekly high-dose gemcitabine (2.200 mg m 72 ) yielded disease control rates of 59 and 66%, respectively (Gebbia et al, 2001;Penz et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of single-agent gemcitabine have reported response rates of 8%-60%, and a median survival time ranging from 6.5 to 11.5 mo [20][21][22][23][24][25] . S-1 is an oral anticancer drug that contains two biochemical modulators, 5-chloro-2,4-dihydroxypridine and potassium oxonate, which improve the tumor-selective toxicity of 5-fluorouracil (5-FU) [26] .…”
Section: Introductionmentioning
confidence: 99%